Compositional analysis of archaeal communities in high and low microbial abundance sponges in the Misool coral reef system, Indonesia - Polónia, Ana Rita Moura; Cleary, Daniel Francis Richard; Coelho, Francisco José Riso da Costa; Becking, Leontine E.; de Voogd, Nicole Joy; Toha, Abdul Hamid A.; Gomes, Newton Carlos Marcial (Marine biology research, 2018)
The high/low microbial abundance (HMA/LMA) dichotomy in sponges has been the subject of several studies over recent years, but few studies have analysed this dichotomy in terms of the sponge archaeal community and function. Using a 16S rRNA gene barcoded pyrosequencing approach and predictive functional analysis (PICRUSt) we compared the archaeal composition, richness and predicted function of one HMA sponge (Xestospongia testudinaria), one LMA sponge (Stylissa carteri) and one sponge species of unknown microbial abundance (Aaptos lobata). Although most of the archaeal sequences were assigned to the Crenarchaeota phylum, S. carteri had the highest percentage of sequences assigned to the Euryarchaeota phylum. Variation among sponge species explained >85% of the variation in archaeal operational taxonomic unit (OTU) composition with each sponge species forming a distinct cluster. There were significant differences in predicted PICRUSt profiles among sponge species, suggesting that archaeal communities present in the studied sponge species may perform different functions. X. testudinaria and A. lobata were similar both in terms of OTU and KEGG orthologues composition, which may indicate that A. lobata is a HMA sponge. Additionally, some of the most enriched functions seem to be related to traits associated with high and low microbial abundance sponges.